READING BEYOND BIAS: USING HISTORICAL DOCUMENTS IN THE SECONDARY CLASSROOM - Sandwell, Ruth (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2003)
ABSTRACT. Social studies and history teachers have, in recent years, taken up with enthusiasm the use of "real" historical documents, (primary sources) in elementary and secondary classrooms across North America. Such documents have an immediacy, and often a personal element, that is more interesting to students than the history found in the average textbook. This paper argues, however, that the pedagogical promise of primary documents is too often limited to a superficial appeal, and the potential of primary documents to stimulate either critical thinking or deeper learning about the past is limited to an analysis of "bias." Beginning with a quick overview of the remarkable potential of primary documents in history education, the paper goes on to provide some practical examples of how teachers can most effectively use them in the classroom. LIRE SANS PRÉJUGÉS: L’UTILISATION DE DOCUMENTS HISTORIQUES DANS LES CLASSES AU SECONDAIRE RÉSUMÉ. Depuis quelques années, dans les écoles primaires et secondaires d’Amérique du Nord, les enseignants d’histoire et de sciences humaines ont adopté, avec enthousiasme, l’utilisation de documents historiques authentiques, appelés aussi documents de premières mains; et ce, dans les écoles d’enseignement primaire et secondaire de toute l’Amérique du Nord. Ce type de documents offre une immédiateté et, fréquemment, une touche de personnalité, qui les rendent plus intéressants que l’histoire telle que présentée dans les livres. Cet article soutient, cependant, que le potentiel pédagogique des documents authentiques est souvent superficiel et que leur utilisation pour stimuler soit l’esprit critique soit un apprentissage en profondeur se limite a une analyse des ’partis pris’. Débutant par un survol du grand potentiel des documents authentiques, cet article poursuit en donnant des exemples pratiques pour utiliser plus efficacement en classe ce type de documents.